Quantifying Macrodispersion in Stratified Porous Formations Using Image Processing and Spatial Moment Analysis (GEOMATE Journal, 2011)
Laboratory dye tracer experiments with a pulse source were conducted under saturated unidirectional flow conditions in a two-dimensional and vertically placed water tank. In tracer experiments, homogeneous and stratified porous formations, which were comprised by a few combinations with three types of soil particles, were of concern to examine the effect of variation of pore structure on macrodispersion phenomena. A new methodology using spatial moment analysis linked with image processing of a dye tracer behavior was developed to estimate macrodispersivities both in longitudinal and transverse directions. These results demonstrated that the ratio of the longitudinal macrodispersivity to the longitudinal microdispersivity ranged from about 2 to about 40. Moreover, it was indicated that the layering of stratified porous formations had an effect on the degree of longitudinal and transverse macrodispersions.